2016
DOI: 10.18632/oncotarget.12867
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenic mimicry in hepatocellular carcinoma contributes to portal vein invasion

Abstract: Portal vein invasion (PVI) is common in hepatocellular carcinoma (HCC) and largely contributes to tumor recurrence after radical tumor resection or liver transplantation. Vasculogenic mimicry (VM) was an independent vascular system lined with tumor cells and associated with poor prognosis of HCC. The present study was conducted to evaluate the relationship between VM and portal vein invasion. A total of 44 HCC cases receiving anatomic liver resection were included in the study and were divided into groups with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Evidence suggests that portal vein invasion (PVI) occurs in the early stage of HCC and is associated with metastasis [2,25,26]. In HCC samples, the Runx2 positive rate in group II was higher than in group I, and highest in group III, which might indicate that Runx2 is associated with HCC cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that portal vein invasion (PVI) occurs in the early stage of HCC and is associated with metastasis [2,25,26]. In HCC samples, the Runx2 positive rate in group II was higher than in group I, and highest in group III, which might indicate that Runx2 is associated with HCC cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wang and colleagues found that the overexpression of Galectin-3 upregulated the expression of the Wnt protein, activated β-catenin, and induced EMT [36]. Studies of the relationship between Runx2 and Galectin-3 demonstrated that Runx2 mediated the expression of Galectin-3 in skeletal tissue, human glioma cells, and human pituitary tumor [2,37,38]. We noticed that, in HCC samples, Runx2 expression is related to Galectin-3 expression (χ 2 = 5.92, p = 0.018); furthermore, we examined the Galectin-3 expression level in HepG2 and SMMC7721 cells Runx2 transfected models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated a higher number of pseudovessels in ASA+Cl-treated mice without any difference in the number of blood vessels between ASA+Cl-treated and control 4T1 mice. Induction of VM in primary tumours of 4T1+ASA/Cl mice was confirmed by higher expression of VE-cadherin (VE-CAD) and secretory leukocyte protease inhibitor (Slpi) (Figure 3H ) with no change in MMP-9, all reported to be markers of VM [ 24 , 22 , 25 , 26 ]. Blood vessels in primary tumours of 4T1+ASA/Cl group were dysfunctional, as evidenced by low expression of the endothelial isoform of nitric oxide synthase (eNOS) and higher expression of Angiopoetin-2 (Ang-2) (Figure 3H ).…”
Section: Resultsmentioning
confidence: 92%
“…HCC is the common malignancy with the most common leading cause of cancer-associated mortality globally, which contributes to the poor prognosis and early intrahepatic and extrahepatic recurrence in HCC patients [ 21 , 22 ]. Although surgical resection accompanied by liver transplantation provides some hope to patients with early stage HCC, the OS of HCC patients is still far from satisfying [ 23 ]. Recently, immunotherapy has become an important and effective complementary approach to conventional HCC treatments [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%